EMPLOYMENT OF THE REGION'S POPULATION: TYPES AND STRUCTURE, ANALYSIS OF INFLUENCING FACTORS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article explores the concept of population employment, its types, and structure. The level of economic activity of the republic's population is statistically analyzed, and differences between regions are identified. Factors affecting the employment structure are grouped, and the role and significance of the economic-geographical location factor in improving population employment are highlighted.
Keywords: population, employment, types of employment, employment structure, economic activity.